(untitled) (Journal of Medical & Health Sciences Review, 2025)
Six villages in the Thorar Tehsil Rawalakot, District Poonch, Azad Jammu & Kashmir, Pakistan, undertook ethnobotanical research. 35 plant species from 26 families were used in the current study by the local inhabitants of the region. The Lamiaceae family contained the most plant species overall. Many ailments are treated with the help of these medicinal herbs. The plant’s local name, flowering season, condition, part used, and diseases treated were noted.